Introductory economics for business and management (London ; New York McGraw-Hill, 2000)
Designed as an introductory text for those new to economics, this book demonstrates the contributions made by economics to organisations. It illustrates how economic factors impact on other business functions such as marketing, IT and purchasing.
Includes bibliographical references and index.
Keywords: Managerial economics